Expression of Recombinant Rat Secretable FNDC5 in Pichia Pastoris and Detection of Its Biological Activity - Zhao, Yi; Li, Hui; Donelan, William; Li, Shiwu; Tang, Dongqi (Frontiers in Endocrinology, 2022)
FNDC5 is the precursor of the myokine irisin proposed to exhibit favorable metabolic activity, including anti-obesity and anti-diabetes effects. The diversity of FNDC5 transcripts has been reported by several studies, but the role and exsitense of these transcripts are not well defined. In our previously study, a novel secretable FNDC5 (sFNDC5) isoform lacking the transmembrane region was found in rat INS-1 cells and multiple rat tissues. In the current study, we established an high yield system for the expression and purification of sFNDC5 in Pichia pastoris, and functional investigations were undertaken using 3T3-L1 cells. We discovered that this new isoform has similar and even stronger biological functions compared with irisin, and this may be due to its more complete structure without cleavage. Hence, we believe that sFNDC5 as the first identified readily secretable derivative can better induce lipolysis and can potentially prevent obesity and related metabolic diseases.